Tracking control using the strip-wise affine transformation: an experimental SoC design - Moustris, George P.; Deliparaschos, Kyriakos M.; Tzafestas, Spyros G. (My University, 2009)
This paper presents the analysis and application of the strip-wise affine map to the path following task for autonomous non-holonomic mobile robots. The mapping was implemented on a Spartan 3-1500 FPGA board with the use of VHDL and advanced EDA tools and was used in field experiments on a Khepera H differential robot. A fully parameterized DFLC previously published by the author has been tailored accordingly for the needs of this design implementation. Experiments were performed using a calibrated camera and a video tracking algorithm in order to extract the actual robot's path, compare it to the odometry solution and analyze the tracker's performance
Keywords: Digital fuzzy logic processor (DFLP); Electronic design automation (EDA); Non-holonomic mobile robots; Path tracking; Strip-wise affine transformation; System-on-a-chip (SoC); Very-high-speed integrated circuits hardware description language (VHDL)